PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA PEGAWAI (STUDI DI KANTOR SEKRETARIAT PEMERINTAH DAERAH KABUPATEN KUTAI TIMUR) - Ernata Hadi Sujito (Universitas 17 Agustus 1945 Samarinda, 2013)
The purpose of the study was to determine: (1) the influence of supervisory of the head to the employee’s discipline; (2) the direct functions supervision of the leadership to the employee’s; and (3) the effect of indirect leader’s supervision to the employee’s work discipline in District Secretariat of East Kutai.The method used in this study is a descriptive analysis of the survey through explanatory method. While data collection techniques used techniques: (1) the study of literature, (2) observation, (3) questionnaire, and (4) interviews and (5) documentation.The results showed that : 1. From the calculation results obtained by the regression equation Y = 2.908 + 0.789 X1 + 0.451 X2. Prediction as a means of labor’s discipline, with the lowest scores work discipline Y = 2.908 + 0.789 (330) + 0.451 (165) = 337,693 and a maximum score of Y = 2.908 + 0.789 (990) + 0.451 (495) = 1007,263. In other words if all variables improved the work discipline scores increased from 337,693 becomes 1007,263.2. Direct and indirect supervision has a positive influence on employee’s discipline. It shows that the satisfactory of supervision, increased employee’s discipline. 3. Both variable, direct and indirect supervision has contributed significantly to the work discipline.4. Variable direct supervision have seen the greatest contribution of the total score of the instrument of questions is a maximum of 990 and the lowest scores is indirect supervision the value is 165.